Orbital Complications of Acute Sinusitis in Pediatric Patients: Management of Chandler III Patients. (April 2022) - Saltagi, Mohamad Z.; Rabbani, Cyrus C.; Patel, Kunal S.; Wannemuehler, Todd J.; Chundury, Rao V.; Illing, Elisa A.; Ting, Jonathan Y.
Background: Surgery is often avoided in the setting of pediatric orbital complications from acute sinusitis unless necessitated by alarming ophthalmological signs. Criteria for surgical intervention are not well-defined. Objective: We aim to review our experiences, management practices and patient outcomes over a ten-year period for Chandler III patients. Methods: A retrospective review was performed from January 1, 2007 through December 31, 2016 of patients treated for orbital symptoms secondary to acute sinusitis at a free-standing tertiary-care pediatric hospital. Results: Of the 186 patients reviewed, 42 Chandler III patients were included. Average age was 82.6 months (SD 50.6) with a slight male predominance (M to F, 1.8 to 1). 27 patients (64.3%) underwent intervention including endoscopic sinus surgery (ESS) with or without orbitotomy. Late surgical intervention (>48hrs from admission) demonstrated significant increase in overall length of stay (LOS) when compared with early surgical intervention and/or medical management (median, 6.9 vs 3.6 vs 3.7 days; p < 0.01). Postoperative LOS was also higher in the late surgery group compared with patients who had surgery within 48 hours of admission, but this did not reach statistical significance [median, 3.8 vs 2.8 days, p= 0.12]. There was no significant difference in overall abscess volume between patients who underwent intervention and those who did not (1019 mm 3 vs 805 mm 3, p = 0.5), but abscess width ≥ 1.2 cm was associated with higher rates of intervention. An alarming extraocular exam was the most common factor associated with surgical intervention. Conclusion: Pediatric subperiosteal orbital abscess may prompt surgical intervention by ESS. An alarming ophthalmologic exam should prompt consideration of early intervention, which may lead to decreased overall and post-operative length of hospital stay. Level of Evidence: 4 Meeting Information: American Rhinologic Society, Fall National Meeting. Chicago, IL, USA. September 8–9, 2017.